Case report: A case of severe lower limb necrotizing fasciitis caused by an insulin injection has been reported - Yang Ma; Jinshuo Tang; Fei Wang; Enbo Liu; Jianlin Zuo (Frontiers in Medicine)
Necrotizing fasciitis (NF) is a rare but life-threatening soft tissue infection, often accompanied by severe systemic toxicity. Early detection and prompt treatment are critical for survival. We report a case of NF in a 53-year-old diabetic woman following a subcutaneous insulin injection in the thigh. The patient presented with severe local pain as the initial symptom, and Escherichia coli was the sole isolated pathogen, which is seldom reported in the current literature. We combined with existing literature and clinical manifestations observed in NF patients at our hospital, offer valuable guidance for clinicians in recognizing and responding to NF.